C‐Met in invasive breast cancer: Is there a relationship with the basal‐like subtype?. Issue 2 (21st October 2013) - Ho‐Yen, Colan M.; Green, Andrew R.; Rakha, Emad A.; Brentnall, Adam R.; Ellis, Ian O.; Kermorgant, Stephanie; Jones, J. L.
Abstract : BACKGROUND: Basal‐like (BL) breast cancer is an aggressive form of breast cancer with limited treatment options. Recent work has identified BL breast cancer as a biologically distinct form of triple‐negative breast cancer, with a worse outlook. The receptor tyrosine kinase c‐Met is a novel therapeutic target associated with reduced survival in breast cancer. Few studies have specifically addressed the association between c‐Met and molecular subtype of breast cancer, yet this is a key consideration when selecting patients for clinical trials. The aim of this study is to evaluate c‐Met expression in a large cohort of invasive breast cancers and in particular, its correlation with molecular subtype. METHODS: Immunohistochemistry for c‐Met was performed and evaluated on 1274 invasive breast cancers using tissue microarray technology. The c‐Met scores were correlated with molecular subtype, survival, and other standard clinicopathological prognostic factors. RESULTS: Multivariate logistic regression showed c‐Met was independently associated with BL status (odds ratio = 6.44, 95% confidence interval = 1.74‐23.78, P  = .005). There was a positive correlation between c‐Met and Her2 ( P  = .005) and an inverse correlation with tumor size ( P  < .001). C‐Met was an independent poor prognostic factor at Cox regression analysis in all subtypes (hazard ratio = 1.85, 95% confidence interval = 1.07‐3.19, P  = .027) and there was a trend toward reduced survival in BL tumors overexpressing c‐Met, but this was not significant. CONCLUSIONS: C‐Met is independently associated with BL breast cancer. In the future, patients with BL tumors should be included in clinical trials of anti‐c‐Met therapy. Cancer 2014;120:163–171 . © 2013 American Cancer Society . Abstract : There is currently no targeted systemic therapy for basal‐like breast cancer, a subtype of invasive breast cancer with a poor prognosis. This study shows that the targetable receptor tyrosine kinase c‐Met is independently associated with basal‐like breast cancer, suggesting that patients with these tumors be included in future clinical trials of c‐Met inhibitors.